Introduction of early childhood mathematics through online learning (e-learning) during the covid-19 pandemic period - Naili Sa‟ida; Tri Kurniawati (Universitas Muhammadiyah Surabaya, 2020)
Abstract. Mathematics is an exact science that is systematically organized, which learns aboutnnumbers, sizes, space and time, and interprets various ideas and conclusions. Mathematical abilities that are introduced to early childhood include: understanding the concept of numbers, algebraic concepts, classification abilities, understanding patterns, geometry, and measurements. During the covid-19 pandemic period, learning was carried out at adistances like the implementation of online learning. In this study, a literature study of various sources was carried out relating to the introduction of mathematics on early childhood through online learning. The result of the literature study shows that the introduction of mathematics on early childhood through online learning can be done by learning through educational games media, Play Kids, social media, and video conference